For this case, to find the roots of the function, we equate to zero.
![x ^ 3 + 2x ^ 2-x-2 = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9o9vmgs2n0kpuiy8wh8fqsthat2ho1btyn.png)
We rewrite how:
![x ^ 3 + 2x ^ 2- (x + 2) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hk8lrr78cmj02y2jxcxo1yr4axmizkn2d7.png)
We factor the maximum common denominator of each group:
![x ^ 2 (x + 2) -1 (x + 2) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4r65hpay0g7gljrqrkuzdzbrbeq3f9zf72.png)
We factor the polynomial, factoring the maximum common denominator
![(x + 2):](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wrdppojhuyydva0k6nxt6u8tnoja3j53ap.png)
![(x + 2) (x ^ 2-1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bfryaq9foqzcd9zd25t26wknczremtrbe7.png)
By definition of perfect squares we have to:
![a ^ 2-b ^ 2 = (a + b) (a-b)](https://img.qammunity.org/2020/formulas/mathematics/high-school/jclbjtt5i3iia9mnsbjr993t6ldd4x0lyx.png)
ON the expression
![(x ^ 2-1):](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p62q89f3l27e5blpj4skbsgn7u0imgq95t.png)
![a = x\\b = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vl3bw1co0gipfw7mhny3f3bevhqjdsuft8.png)
So:
![(x ^ 2-1) = (x + 1) (x-1)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4c4rbonx6n232m9fo3cyuxhqee1ly8irti.png)
Thus, the factorization of the polynomial is:
![(x + 2) (x + 1) (x-1) = 0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8e1f95phbgmxhk2qr5e3e9eg5kyquyusgc.png)
![x_ {1} = - 2\\x_ {2} = - 1\\x_ {3} = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ypox4rhi9m5wk0o73pedx53wza3mhx7jo.png)
ANswer:
![x_ {1} = - 2\\x_ {2} = - 1\\x_ {3} = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8ypox4rhi9m5wk0o73pedx53wza3mhx7jo.png)